Studi Lubricant Properties (Density) Dengan Penambahan Calcium Hypochlorite - Rochman Saefudin; Nazaruddin Nazaruddin; Dedy Masnur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The need of unrenewable source synthetic lubricating oil is increasing thus many researchs have been conducted to find the substitute. Palm oil is one of alternatives, however direct use of palm oil as a lubricant remain cause problems namely high density of palm oil leads to imperfect lubrication. It is necessary to find the correct additif which is able to improve the lubricant properties. This research evaluate the addition of calcium hypochlorite to density of Palm Oil. The samples were prepared in 250 ml volume in three volume ratios which are (90:10), (85:15), and (80:20). The mixing process is conducted at 100 rpm and heated 120°C in 2 hours.The density test resultshows that calcium hypochlorite decreases the density of palm oil as follows 901 kg/m3 for 90:10,898 kg/m3for 80:15, and 897 kg/m3for 80:20. Keywords: Lubricants, Palm Oil, Calcium Hypochlorite, Density